Isolated Native Tricuspid Valve Endocarditis Caused by Viridans Streptococcus - John Swiston; Stephen D Shafran; Narmin Kassam (Canadian Journal of Infectious Diseases)
The present report describes a case of native tricuspid valve endocarditis caused by viridans group streptococcus in a 43-year-old man who had recently undergone dental extraction. The patient had no history of intravenous drug use, heart disease or right heart catheterization. Although there have been scattered reports of unusual organisms, to the authors' knowledge, this is the first case of viridans group streptococcal endocarditis involving only the tricuspid valve after dental manipulation.